Gonad maturation of sepat mutiara (trichogaster leeri blkr) with different feeding treatmen - Habibi '; Sukendi '; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted from Maret – Mei 2013 in laboratory ofbreeding Fishery and Marine Science Faculty of Riau University. The aim of thisresearch was to investigate suitable feed for the maturation of the gonads of sepatmutiara (Trichogaster leeri Blkr) reared with different feeding treatment such asGonad Maturity Level (TKG), gonad maturation index (IKG), fecundity, eggdiameter and egg maturation. The research method used was CompletelyRandomized Design (CDR) with three treatments and three replications. Thetreatment in this study were P1 (Tubifex sp), P2 (Shrimp pellet), P3 (Shrimp pellet+ Vitamin E).The result showed that good feed for the maturation of the gonads wasshrimp pellets + Vitamin E, total fish reached TKG IV 13 tails , index gonadsomatic 9,32 %, fecundity of 2646 eggs, egg diameter 0.70 mm. The temperaturerange from 26-28 0 C, pH 5-6, dissolved oxygen 4-5 ppm.Keyword: different feed, Gonad maturation, Trichogaster leeri Blkr